Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw dengan Media Komik Strip untuk Meningkatkan Aktivitas dan Hasil Belajar Kimia Siswa SMK Negeri 4 Gowa - Zaenab, Zaenab (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to describe the application of the jigsaw cooperative model with comic strip media to increase students' activity and chemistry learning outcomes. This research method used classroom action research, including four stages of implementation, namely: planning, action, observation, and reflection. The subjects in this study were students of class X TKJ 3 SMK Negeri 4 Gowa with a total of 35 students. The research instrument used observation, tests, and documentation. The data analysis technique used descriptive qualitative and quantitative. The results of this study indicate that the mean score of students obtained after the first cycle was 5.9 which was at moderate intervals. Descriptively the results of this study also revealed that the results of learning chemistry class X TKJ3 SMK Negeri 4 Gowa who took the jigsaw cooperative learning type using comic strip media in cycle II was 7.3 which was at high intervals. In cycle I, there were no students who got very high scores and there were still students who had scores in the low category, namely around 28.5 or about 10 students. In Cycle II, students who scored in the very high category were around 14.3 and no students who scored in the low or very low category were found. In general, it can be said that there is an increase in student learning outcomes through the application of the jigsaw cooperative learning model at SMK Negeri 4 Gowa.